2007
DOI: 10.1007/s00134-007-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure support ventilation and positive end expiratory pressure on the rapid shallow breathing index in intensive care unit patients

Abstract: In the same patient the use of PSV and/or PEEP as low as 5 cmH2O can influence the RSBI. In contrast, changes in FIO2 may have no effect on the RSBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
5
27
0
4
Order By: Relevance
“…In contrast, some clinicians leave the patient connected to the ventilator and calculate f/V T with the respiratory rate measured by the ventilator. 65 But because the ventilator does not detect ineffective efforts, the ventilator-measured respiratory rate will be lower than the true respiratory rate. As an example, if V T is 0.3 L and the ventilator-measured respiratory rate is 21 breaths/min, then f/V T is 70 breaths/min/L, which suggests that the patient is likely to pass a spontaneous breathing test.…”
Section: Effect Of Patient-ventilator Asynchrony On Outcomesmentioning
confidence: 99%
“…In contrast, some clinicians leave the patient connected to the ventilator and calculate f/V T with the respiratory rate measured by the ventilator. 65 But because the ventilator does not detect ineffective efforts, the ventilator-measured respiratory rate will be lower than the true respiratory rate. As an example, if V T is 0.3 L and the ventilator-measured respiratory rate is 21 breaths/min, then f/V T is 70 breaths/min/L, which suggests that the patient is likely to pass a spontaneous breathing test.…”
Section: Effect Of Patient-ventilator Asynchrony On Outcomesmentioning
confidence: 99%
“…[5][6][7][8][9] The rapid shallow breathing index (RSBI) 3,10 and the out-comes of a spontaneous breathing trial (SBT) with either a T-piece or low-level pressure support ventilation (PSV) 11 are commonly used clinical methods. However, various thresholds and sensitivities of the RSBI exist among different patient populations and measurement conditions, [12][13][14] and 25-40% of patients who pass an SBT develop failure signs after being weaned from mechanical ventilation. 10,15,16 Weaning patients from ventilatory support is a complex issue.…”
Section: Introductionmentioning
confidence: 99%
“…They found that in the same patient with the use of PSV and/or PEEP as low as 5 cm H 2 0, smaller RSBI values were identified when compared with the ones measured during the T-piece. They found no effects from changes in FiO 2 on the RSBI values (21 O, the RSBI and f values increased and VT decreased, but this was not statistically significant. When PEEP was adjusted to 0, RSBI increased, but there was no significant change in f and VT values as the PS value was decreased.…”
Section: Yılmaz Et Al Rapid Shallow Breathing Index In Different Prementioning
confidence: 90%
“…These parameters did not vary when PSV was reduced from PSV 10 cm H 2 O to PSV 5 cm H 2 O (20). In a prospective study by El-Khatib et al (21), RSBI values under various ventilator support settings prior to extubation were evaluated. Similar to our study, they compared RSBI measured as 0 cm H 2 0 PSV/5 cm H 2 0 PEEP and 40% FiO 2 , 0 cm H 2 0 PSV/5 cm H 2 0 PEEP and 21% FiO 2 , and a 1 minute spontaneously breathing room air trial off the ventilator (T-piece).…”
Section: Yılmaz Et Al Rapid Shallow Breathing Index In Different Prementioning
confidence: 99%